The endophytic fungus Penicillium oxalicum isolated from Ligusticum chuanxiong Hort possesses DNA damage-protecting potential and increases stress resistance properties in Caenorhabditis elegans - Tang, Zizhong; Qin, Yihan; Wang, Yueyu; Lin, Wenjie; Wang, Qing; Shen, Nayu; Xiao, Yirong; Chen, Hong; Chen, Hui; Bu, Tongliang; Li, Qingfeng; Yao, Huipeng; et al. (Frontiers in Pharmacology, 2022)
The chemical composition and antioxidant activity of the extracts (POE) of Penicillium oxalate isolated from Ligusticum chuanxiong Hort have been investigated. However, the biological activity of POE is limited, and its antioxidant, stress resistance and DNA protection effects in vivo is unclear. The current study aims to explore the beneficial effects of POE on DNA damage protection in pBR322 plasmid and lymphocytes, and stress resistance in the C. elegans. The results showed that POE increased the survival rate of C. elegans under 35° C, UV and H2O2 stress, attenuated ROS and MDA accumulation, and enhanced the activity of some important enzymes (SOD, CTA and GSH-PX). In addition, the POE-mediated stress resistance involved the upregulating of the expression of the sod-3, sod-5, gst-4, ctl-1, ctl-2, daf-16, hsp-16.1, hsp-16.2 and hsf-1 genes and acted dependently daf-16 and hsf-1 rather than skn-1. Moreover, POE reduced lipofuscin levels but did not prolong the lifespan or damage growth, reproduction and locomotion of C. elegans. In addition, POE also showed a protective effect against DNA scission in pBR322 plasmid and lymphocytes. These results suggested that Penicillium oxalate extracts have significant anti-stress and DNA protection potentials and may be a potential drug candidate in the pharmaceutical field, thus greatly broadening the understanding of the biological effects of the endophytic fungus Penicillium oxalate.